Compression Therapy Competence, Patient Education Practices, and Guideline Adherence in Venous Leg Ulcer Nursing Care: A Cross-Sectional Mediation Study - Asmat Burhan; Hadi Kusuma; Rubiyanto Warja; Asrizal (Indonesian Science Media, 2026)
Background: Guideline adherence in venous leg ulcer nursing care requires technical competence, structured patient education, and consistent wound assessment. However, evidence on how compression therapy competence relates to adherence through patient education practices remains limited in hospital-based nursing settings Aim: To examine factors associated with guideline adherence and the mediating role of patient education practices among nurses Approach: This cross-sectional study included 131 nurses recruited by consecutive sampling from March to May 2026. Eligible participants were registered nurses involved in venous leg ulcer or wound-related care. Linear regression and mediation analysis were used to examine adjusted associations Results: Total nurses who completed the study was 131. The mean (SD) age was 33.8 (6.7) years, and 96 participants (73.3%) were women. The mean (SD) guideline adherence score was 74.6 (9.8). Higher patient education practices were associated with guideline adherence (adjusted B, 2.26; 95% CI, 0.73-3.79; P = .004), as were compression therapy competence (adjusted B, 1.58; 95% CI, 0.15-3.01; P = .031) and wound assessment quality (adjusted B, 1.82; 95% CI, 0.32-3.32; P = .018). Patient education practices partially mediated the association between compression therapy competence and guideline adherence Conclusions: Compression therapy competence, patient education practices, and wound assessment quality were associated with guideline adherence in venous leg ulcer nursing care Implication for Nursing Practice: Structured compression training, standardized wound assessment, and patient education checklists may support more consistent venous leg ulcer nursing care, although longitudinal evidence is needed